Mencegah Gerakan Radikalisme, Fundamentalisme, Terorisme Melalui Kurikulum Pendidikan Agama Islam - Alipah Alipah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Radicalism, Fundamentalism, and Religious Terrorism lead to acts of violence against the background of the phenomenon of religious fanaticism which will lead to a partial interpretation of the concept of jihad in Islam. The logical consequence of this interpretation is the juxtaposition of terrorism as the fruit of radicalism. Radical ideology or understanding of radicalism has developed so widely that it penetrates the boundaries of formal and non-formal education. The research used in this research is library research or library research where this research examines books, articles, and other information to be collected, processed, and concluded in order to find answers to the problems in this research. This paper seeks to reveal how the noble value of Islamic Religious Education (PAI) is in preventing radicalism, fundamentalism and Islamic terrorism.